Physical chess game tracking using Raspberry Pi - Yee, Wei Jun (2024)
With the popularity in chess increases exponentially caused by the advancement of information technology where there are many chess players were influenced by online chess streamer and got interest in chess. Due to this fact, there are many chess tournaments being organized worldwide no matter the scale of them. With the use of the current technology in tracking and broadcasting the chess game which is using electric chess board with uniquely manufactured chess pieces with unique patented sensor technology, it is costly to track and broadcast every single chess game begin played in the tournament on a website. Hence, a novel alternative way of tracking and broadcasting a chess game is proposed in this project by using Raspberry Pi with compatible camera module and detection and recognition model installed on it. The Raspberry Pi will detect chess move and relay the move to a web application where it will change the state of the digital chess board with the chess move received. Additionally, it will also store the move in a database for future analysis. By using the approach proposed, the cost of tracking a chess game and broadcasting it will be drastically decreases, thus, the overall cost of organizing a chess tournament will also decreases.